Peran Kepemimpinan, Motivasi, Dan Kepuasan Kerja Dalam Meningkatkan Kinerja Karyawan - Maghfiroh, Nurul; Turmudhi, Anis (Jurnal Ilmiah Mahasiswa Perbankan Syariah (JIMPA), 2025)
This study aims to analyze the influence of leadership, motivation, and job satisfaction on employee performance at CV Adelindo Abadi in Semarang City. The background of this research is based on the importance of human resources as a key factor in achieving company goals, where employee performance is strongly influenced by the quality of leadership, the level of motivation, and the job satisfaction experienced by employees. The research method used is quantitative with a descriptive approach. Data were collected through questionnaires distributed to employees and analyzed using multiple linear regression. The results of the study indicate that leadership, motivation, and job satisfaction both simultaneously and partially have a positive and significant effect on employee performance. These findings suggest that improvements in leadership, motivation, and job satisfaction can lead to better employee performance within the company. Therefore, it is recommended that management continue to develop effective leadership styles, provide appropriate motivation, and create a supportive work environment to optimize employee performance.